2009
DOI: 10.1016/j.jcrs.2008.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Role of combined cataract surgery and intravitreal bevacizumab injection in preventing progression of diabetic retinopathy

Abstract: Intravitreal administration of 1.25 mg bevacizumab at the time of cataract surgery was safe and effective in preventing the progression of DR and diabetic maculopathy in patients with cataract and DR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 41 publications
(37 reference statements)
1
48
1
Order By: Relevance
“…Kim et al 21 found no difference in diabetic retinopathy progression 6 months postoperatively between a group receiving sub-Tenon triamcinolone and a control group (P Z .08). Cheema et al 26 evaluated the effect of intravitreal bevacizumab injected during cataract surgery on postoperative diabetic retinopathy progression; progression occurred in 45.45% of eyes in the control group and 11.42% of eyes in the treatment group (P Z .002).…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al 21 found no difference in diabetic retinopathy progression 6 months postoperatively between a group receiving sub-Tenon triamcinolone and a control group (P Z .08). Cheema et al 26 evaluated the effect of intravitreal bevacizumab injected during cataract surgery on postoperative diabetic retinopathy progression; progression occurred in 45.45% of eyes in the control group and 11.42% of eyes in the treatment group (P Z .002).…”
Section: Discussionmentioning
confidence: 99%
“…Cheema and colleagues randomized 68 eyes with any type of DR to 1.25 mg bevacizumab at the conclusion of cataract surgery or surgery with no injection [91]. At baseline, 39 eyes had CSME, and all were treated pre-operatively with focal laser.…”
Section: Bevacizumab As An Adjunct To Cataract Surgerymentioning
confidence: 99%
“…This involves argon laser panretinal photocoagulation as the primary treatment for proliferative retinopathy and focal macular laser for clinically significant macular edema. Additional treatment involves intravitreal injection of vascular endothelial growth factor inhibiting medications and steroids (Cheema et al, 2009;Lam et al, 2005). The patient should also achieve a tight control of systemic blood glucose, and this should be demonstrated in the patient's hemoglobin A1c levels (Suto et al, 2006).…”
Section: Diabetic Retinopathymentioning
confidence: 99%